The Factors Affecting on Woman's Participation in Family Decision – making in Al Kut a Study in the Geography of Population - أمل عطيوي عباس, م.د. (lark, 2021)
The present study seeks to, the most important influencing factors on the women's participation in family decision-making in the city of Al Kut, including the age group of both the husband and wife, age at the time of marriage, education of the spouses, women's profession, size of the family. The study has focused attention on those decisions related to women's education and educating their sons as well as decisions relevant to the work of women, regulating family budget, and other related decisions with the reproductive health of women. It is worthy to mention that the present study has adopted the descriptive and analytic approach, together with the qualitative method. Additionally, some statistical methods have been utilized, like Qi-Square, Pearson Correlation Coefficient to reveal the association between some characteristics of women and their ability to make family decisions.